Antibacterial Activities and Chemical Composition of Essential Oils from Sweet Orange (Citrus sinensis), Lemon Grass (Cymbopogon citratus), and Lime (Citrus aurantifolia) Peels - Omoboye, Olumide; Sotola, Toyosi; Balogun, Olaoye; Bamigbade, Ololade; Oluwole, Olusola; Odeyemi, Adebowale; Oluduro, Anthonia (UI Scholars Hub, 2024)
This study investigated the chemical composition and antibacterial activities of lime Citrus aurantifolia (Cc) and lemon grass Cymbopogon citratus (Ca) essential oils (EOs). Standard methods were used to determine their minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC), and gas chromatography–mass spectrometry was used to determine their composition. Each EO and their combination showed promising results in treating test bacterial infections. Cc EO showed the largest inhibition zone diameter (43 mm) against Staphylococcus aureus and Serratia marcescens, and Ca EO showed the largest (30 mm) and smallest (12 mm) inhibition zone diameters against Bacillus stearothermophilus and S. marcescens, respectively. The combination of Cc EO and Ca EO (1:1) resulted in the largest (45 mm) and smallest (8 mm) inhibition zone diameters against Klebsiella pneumoniae and Salmonella typhimurium, respectively. The MIC of Cc EO ranged from 0.78% to 6.25%, and its MBC ranged from 3.13% to 12.50%. The MIC and MBC of combined Cc EO and Ca EO ranged from 0.78% to 6.25% and from 1.56% to 12.5%, respectively. The major components of Cc EO and Ca EO were neral (44.98%) and D-limonene (56.02%). Overall, the combination of lime and lemon grass EOs performed well compared to streptomycin, making them suitable for treating test bacterial infections.